DARI BUMI KE NURANI: SINERGI SDGS, PRAMUKA, DAN BIMBINGAN TAKWA DALAM SATU PETUALANGAN SDIT CENDEKIA PURWAKARTA - Alma Amelia; Ashfa Nurul Mahmudah; Casya Insania; Friseza Nayla Aribah Zahra; Nisha Fitria; Nurfadillah Hasan (STKIP Subang, 2025)
Environmental issues remain significant challenges in many areas. The low level of environmental literacy and students’ involvement in environmental conservation practices highlights the importance of implementing practical environmental education from an early age. This community service program aims to enhance environmental literacy and students’ environmental awareness at SDIT Cendekia Purwakarta through hands-on learning activities integrated with the Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education) and SDG 15 (Life on Land). The program employed a descriptive participatory approach using a station-based (Pos to Pos) learning model consisting of three activity zones: the Green Zone (school greening activities), the Collaboration Zone (3R-based waste management practices), and the Quiz Zone (learning evaluation). The results indicate high student enthusiasm and active participation in all activities, improved understanding of environmental conservation concepts, and the development of responsibility and collaborative skills. This program demonstrates that practice-based environmental education is effective in fostering sustainable behaviors and supporting the achievement of the SDGs in elementary school settings.